LOANS BORROWING AND SOCIAL WELLBEING OF ADMINISTRATION POLICE SERVICE OFFICERS IN EMBAKASI SUB COUNTY, NAIROBI CITY COUNTY, KENYA - Anzetse, Hezborn Michael; Wambua, Dr. Peter Philip (Journal of Public Policy and Administration, 2020)
Purpose: The purpose of the study was to determine the effects of loans borrowing on Social Well-being of Administration Police Service Officers in Embakasi Sub-County, in Nairobi County, Kenya. Methodology: The researcher employed a descriptive research design. The research was carried out at Embakasi Sub County which has 11 Administration Police posts, with a total of 175 Officers. A sample size of 65 Officers was selected using stratified sampling technique. This sample made 37% of the target population. Questionnaires and Interviews were used to collect data. The quantitative data was analysed using descriptive statistics like the mean, mode and standard deviation. Findings: The findings revealed that loan borrowing is indeed good for the Administration Police Service Officers, since it has enabled them do great things, including, buying premises, constructing houses, buying vehicles, both commercial and personal and even starting a business. However, besides the loans being a noble idea, it has to some extent been because of the way it has been utilized, resulted in break-ups of families, some officers have lost their jobs and it has had a negative impact on social integration between officers themselves and even with the community at large. Unique contribution to theory, practice and policy: The study recommends that: Government should increase the loans extended to Administration Police Service Officers to rational level in order to improve their wellbeing and enhance service delivery in the service; encouragement of police officers to take SACCO loans in order to improve their wellbeing; Microfinance institutions should give loans to administration police officers in order to improve their social wellbeing; Administration police service officers should borrow loans and use them for the right purpose in order to improve their social wellbeing.